ANALISIS TEKNOLOGI FINANSIAL SAAT PANDEMI COVID-19 TERHADAP KINERJA PERBANKAN DI INDONESIA - Tri Kunawangsih Purnamaningrum; Antyo Pracoyo (Media Ekonomi, 2023)
The purpose of this study is to analyze the performance of banks listed on the Indonesia Stock Exchange utilizing various technology platforms during the pandemic COVID-19. The independent variables used in both research models consist of ITF, LDR, and NPL. This study uses two models, in the first model the dependent variable is ROA, while in the second model, BOPO is the dependent variable. In order to fulfill the objectives of this study, the sample used was 40 conventional banks which during the observation period were listed on the Indonesia Stock Exchange. In this study used quarterly data throughout 2020, consisting of quarters 1, 2, 3, and 4. Based on the initial data presented when processed, they were forced to discard some of the available data for both the first and second models. The mechanism for deleting processed data is because the data is included in the outlier category. For data categorized as outliers, a data reduction mechanism is carried out